Delay and cost overrun in road construction projects in Jordan - Al-Hazim, Nabil; abusalem, zaydoun (International Journal of Engineering and Technology, 2015)
This study aims to identify the most important factors that cause delay in road construction projects in Jordan, which results in cost and time overrun allocated for this type of engineering projects and cause critical problems for both the developer and the contractor. The gap between the cost at completion and that originally estimated, known as cost overrun, can be regarded as one of the most important parameters reflecting the success of projects. In the public sector, money spent on project change orders results in increased construction time which in return reduces the number and size of the projects that can be completed during any given fiscal year. To achieve this goal, the documents and the final reports for several sample projects implemented over the years 2000 to 2008 were analyzed. All the projects were administered by the same organization taken from Jordan Ministry of Rural and Public Works. The results of this study can assist highway officials in their design, planning, scheduling and projects completions so that necessary actions can be taken to control these overruns in future projects. The study showed that 19 factors might cause delays of road construction projects as defined through a detailed literature review. The analysis of the study indicated that the top causes affecting time and cost overrun in road construction projects in Jordan are Terrain and Weather conditions.